BFO Theory Principles and New Opportunities for Company Value and Risk Management - Laptev, Sergey V. (Journal of Reviews on Global Economics, 2018)
This article explores the significance and additional capabilities of new principles for analyzing the capital structure and calculating the market value of a company. These principles are being developed as part of Brusov-Filatova-Orekhova theory (BFO) and are aimed at considering the diverse factors which affect the market value of companies. These principles include accounting and calculating the value of a company within its lifecycle; focusing on a more complete and differentiated assessment of a company's risks and their consideration in the course of running the company and managing its market value, compared to in the Modigliani-Miller theory. According to these principles, one should take into account and assess all significant possible effects that are formed in the course of running a company with regard to its value, even if such effects do not explicitly materialize until a certain point of time, are not taken into account during the market appraisal and are used during the company valuation as some kind of a virtual, imaginary value. Changes in the calculation of such virtual values of a company value may suggest that risks have accumulated both at the micro and macro level of economy. Studying the mechanisms created in the course of running a company and aimed at transforming the virtual values of its value into real positive or negative changes in the value can be an important tool for enhancing the effectiveness of risk management in companies and economic systems.